Efficacy of Zingiber cassumunar Roxb (Phlai capsule) Compare with Loratadine as Treatment in Allergic Rhinitis Patients (Preliminary Results) - Thanee, Patrada; Lertnawapan, Ratchaya; Sritipsukho, Paskorn; Nanthapisal, Sira; Kulalert, Prapasri; Tanticharoenwiwat, Pattara; Achararit, Nitchanan; Tantilipikorn, Pongsakorn; Poachanukoon, Orapan (Asian Medical Journal and Alternative Medicine, 2022)
Introduction: Phlai capsules can inhibit skin reactivity in allergic rhinitis patients. Objectives: The aim of this study was to compare the efficacy of Phlai capsules with Loratadine in allergic rhinitis patients. Methods: This was a multi-center, prospective, randomized, double-blinded, placebo-controlled study in 50 patients, aged 18-50 years old, who randomly received 4 mg or 8 mg Phlai capsules or Loratadine for 8 weeks. The primary efficacy endpoint was Total Symptoms Score at 4 and 8 weeks. The secondary endpoints were peak nasal inspiratory flow and quality of life. Results: Demographic data was similar between groups. The change in 6-Total symptoms score decreased significantly from baseline. Peak nasal inspiratory flow increased with no significant differences between groups. According to the RCQ-36 questionnaire, there wassignificant improvement in quality of life for every domain, including sleep and emotion. Conclusions: Phlai capsules reduced rhinitis symptoms and improved quality of life.